Development of a Maritime-Based STEAM Laboratory Book to Improve Students’ Problem-Solving Skills - Hartika Sari; Suryo Hartanto; Albert Efendi Pohan (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Nahdlatul Wathan Mataram, 2025)
The lack of contextual and integrative learning media is one of the challenges in enhancing maritime literacy among students. This study aims to develop a maritime-based STEAM laboratory book that is valid, practical, and effective in improving students' understanding of maritime concepts and their problem-solving skills in science learning. The study used the Research and Development (R&D) method using the ADDIE model, which includes the stages of Analysis, Design, Development, Implementation, and Evaluation. The developed product was designed based on the STEAM approach with six stages: focus, detail, discovery, implementation, presentation, and link. The validity of the book was obtained from expert evaluations, with scores of 81% for content and 85% for design, both categorized as highly valid. The practicality of the book was assessed based on teacher responses (92%) and student responses (85.4%), both of which were classified as highly practical. The effectiveness of the product was shown by student responses (83.7%),and there was an improvement in problem-solving skills